2022
DOI: 10.1002/qute.202100147
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Light Shadow Imaging Using Quadrature‐Noise Detection with a Camera

Abstract: This paper experimentally demonstrates an imaging technique based on quadrature noise modification after interaction with an opaque object. By using a homodyne‐like detection scheme, the detrimental effect of the camera dark noise is eliminated, making this approach particularly attractive for imaging scenarios which require weak illumination. As an example, the image of an object illuminated with a squeezed vacuum is reconstructed using a total of 800 probing photons, utilizing less than one photon per frame … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The study reported here sheds light on some complex mode dynamics, transition to instability, and correlations in driven dispersive nonlinear resonators. The multimode and spatially-distinct nature of the correlations in the AMWM studied here can also find applications in study of phase transition 17 , multimode optical switching 18 , quantum imaging 32 , 33 , and quantum communications 7 , 34 using room-temperature sources. For example, by reflecting one beam from an object and detecting both correlated beams on a CCD camera, the intensity correlations can be used to measure change in the reflectivity beyond the state-of-the-art classical devices 35 .…”
Section: Introductionmentioning
confidence: 84%
“…The study reported here sheds light on some complex mode dynamics, transition to instability, and correlations in driven dispersive nonlinear resonators. The multimode and spatially-distinct nature of the correlations in the AMWM studied here can also find applications in study of phase transition 17 , multimode optical switching 18 , quantum imaging 32 , 33 , and quantum communications 7 , 34 using room-temperature sources. For example, by reflecting one beam from an object and detecting both correlated beams on a CCD camera, the intensity correlations can be used to measure change in the reflectivity beyond the state-of-the-art classical devices 35 .…”
Section: Introductionmentioning
confidence: 84%
“…We did not take any additional steps to reduce the probe beam power before the magnetometery cell. However, it is straightforward to reduce it without compromising the amount of noise suppression using a simple Mach-Zender interferometer [34], and our measurements suggest that the magnetometer sensitivity may be improved with additional optimization of the mean probe power.…”
mentioning
confidence: 95%